Peningkatan Kemampuan Mengenal Huruf Alfabet Melalui Media Puzzle Pada Murid Down Syndrome Di SLB Negeri 1 Barru - Sri Yuliana; Abdul Hadis; Usman Usman (JURNAL ORTO DIDAKTIKA, 2023)
Negeri 1 Barru to recognize the letters of the alphabet. The formulation of this research problem is. How to find out the letters of the alphabet through puzzle media for students with Down syndrome Class V at SLB Negeri 1 Barru based on condition analysis and analysis between conditions? given treatment, 2) description of recognizing the letters of the alphabet in class V down syndrome students when treatment was given through puzzle media, 3) description of the ability to recognize letters of the alphabet in class 5 down syndrome students after using puzzle media, 4) description of ability to recognize letters of the alphabet in down syndrome students syndrome class V through puzzle media. This study uses the Single Subject Research (SSR) experimental method using the A-B-A research design. The data acquisition technique used is an action test. The subject of this research is one of the students at SLB Negeri 1 Barru class V with the initials AN. The conclusions of this study are as follows: 1) The ability to recognize letters of the alphabet in Down syndrome students before treatment is given is still very low, 2) The ability to recognize letters of the alphabet in Down syndrome students during treatment through puzzle media has increased to a very good category, 3) The ability to recognize the letters of the alphabet in Down syndrome students after being given increased compared to before being given treatment and increased to the very good category, 4) Based on the analysis between conditions, namely in the condition before the treatment was given, the student's ability was still very low to be increased to the very good category in the condition dives were given treatment through puzzle media, and in the condition after being given treatment the students' abilities remained in the very good category.